Pengaruh Kemudahan Penggunaan E-Filing, Kesadaran Wajib Pajak, dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi - Nuriyah Shinta Devi; Suci Rohayati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to analyze the influence of ease of e-filing, taxpayer awareness, and tax sanctions on individual taxpayer compliance. The population in this research is individual taxpayers registered at KPP Pratama North Sidoarjo. Determining the sample in this study used a purposive sampling method and the sample size was 100 people. The type of data used in this research is primary data in the form of respondents' answers from questionnaires that have been distributed. The analysis technique in this research uses multiple linear regression analysis. The results of this research show that simultaneously the ease of e-filing, taxpayer awareness, and tax sanctions have a significant positive effect on individual taxpayer compliance. Partially, ease of e-filing, taxpayer awareness, and tax sanctions have a significant positive effect on individual taxpayer compliance. This means that the more taxpayers who use the e-filing system, the higher the awareness of taxpayers and tax sanctions, the more individual taxpayer compliance will also increase.